1985
DOI: 10.1099/0022-1317-66-6-1263
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleotide Sequence of the Pieris brassicae Granulosis Virus Granulin Gene

Abstract: SUMMARYTwo overlapping restriction fragments containing the Pieris brassicae granulosis virus (GV) granulin gene were cloned into plasmids. The regions containing the coding region and the 5" and 3' flanking regions were subcloned into M 13 and sequenced. The nucleotide sequence data were compared to those for the granulin gene from the Trichoplusia ni GV and the polyhedrin gene from the Autographa californica nuclear polyhedrosis virus (AcMNPV). The amino acid sequences derived from these DNA sequences indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The probe hybridized to HindlII-B or -C, BamHI-H and -D, -E, -F or -G, and EcoRI-D or -E. Examination of the map showed that the granulin gene must therefore lie within HindlII-B, BamHI-I, -F and -N (which had run off the gel) and EcoRI-E. This was in agreement with the sequence of the ArGV 1 granulin gene obtained by Chakerian et al (1985). The zero point for the map was taken as the first base of the coding region and the map was orientated so that the direction of granulin gene transcription was the same as the polyhedrin gene in AcMNPV.…”
supporting
confidence: 70%
“…The probe hybridized to HindlII-B or -C, BamHI-H and -D, -E, -F or -G, and EcoRI-D or -E. Examination of the map showed that the granulin gene must therefore lie within HindlII-B, BamHI-I, -F and -N (which had run off the gel) and EcoRI-E. This was in agreement with the sequence of the ArGV 1 granulin gene obtained by Chakerian et al (1985). The zero point for the map was taken as the first base of the coding region and the map was orientated so that the direction of granulin gene transcription was the same as the polyhedrin gene in AcMNPV.…”
supporting
confidence: 70%
“…This consensus sequence is also present in both of the pl0 genes which have been analysed [AcMNPV, Kuzio et al, 1984;Liibbert & Doerfter, 1984: Orgyia pseudotsugata (Op) MNPV, Leisy et al, 1986c]. The subgroup B baculoviruses (granulosis viruses; GVs) also have the same consensus sequence upstream of the granulin gene, which encodes an occlusion body protein of similar function to polyhedrin (Akiyoshi et al, 1985;Chakerian et al, 1985). The polyhedrin mRNA start sites have been accurately determined for AcMNPV (Howard et al, 1986) and OpMNPV (Leisy et al, 1986a).…”
Section: Short Communicationmentioning
confidence: 98%
“…4). This sequence appears to be conserved throughout the Baculoviridae: related sequences have been described upstream of granulin genes (Akiyoshi et al, 1985;Chakerian et al, 1985), AcMNPV 10K (Kuzio et al, 1984) and OpMNPV 10K (D. Leisy et al, unpublished observations) protein genes and the polyhedrin genes of AcMNPV (Hooft van Iddekinge et al, 1983), Bombyx mori NPV (BmNPV) (Iatrou et al, 1985) and OpMNPV (D. Leisy et al, unpublished observations). All hypertranscribed baculovirus genes examined (polyhedrin and 10K), have mRNA initiation sites at or very near this conserved sequence (Hooft van Iddekinge et al, 1983;Kuzio et al, 1984;D.…”
Section: Genome Map and Location Of The Polyhedrin Genementioning
confidence: 99%